Research Progress of Fucoidan in Improving Obesity and Complications - Yang WU; Yong WU; Hongbing CHEN; Xueling JIN; Daowu HUANG; Xiumei YU; Shuangyan ZHENG (Shipin gongye ke-ji)
Obesity, a serious and growing issue, is associated with metabolic complications like dyslipidemia, non-alcoholic fatty liver disease, oxidative stress, and systemic inflammation. These complications pose a severe threat to human health. Fucoidan, a bioactive polysaccharide extracted from brown algae and certain marine invertebrates, holds the potential to ameliorate obesity and its associated diseases, thus becoming a current research hotspot. As a dietary supplement, fucoidan enhances obesity by modulating fat synthesis and breakdown, adipocyte differentiation and basal energy metabolism, as well as the abundance and beneficial bacteria ratio of intestinal microbiota. Additionally, fucoidan alleviates obesity-related diseases by reducing liver fat accumulation and lipotoxicity, lowering blood lipid levels and insulin resistance, promoting macrophage M1 to M2 polarization and the release of anti-inflammatory cytokines, and eliminating reactive oxygen species and lipid peroxidation products. This article presents some of the current applications of fucoidan in the food, medicine, and medical fields, and discusses the existing limitations, providing references for further research on fucoidan efficacy and new product development.